Gynecologic infection rates after ablation treatment for cervical intraepithelial neoplasia grade 2 and higher (CIN2+): Secondary analysis of a non-inferiority randomized trial. - Rachel Masch; Gabriel Conzuelo-Rodriguez; Jameson A Mitchell; Karla Alfaro; Montserrat Soler; Luis F Chavez; Suhui Wu; Jinfen Sun; Longhua Hu; Dayana Marinela-Hernandez; Todd A Alonzo; Juan C Felix; et al. (Public Library of Science (PLoS), 2024)
Although concerns have been raised regarding potential infection and morbidity in women undergoing ablation treatment for cervical precancer in low- and middle-income countries (LMIC), there is extremely limited data to substantiate this claim. This is a secondary analysis of a randomized non-inferiority trial (id: NCT03084081) that compares the efficacy and safety of three ablation treatments for biopsy-confirmed cervical intraepithelial neoplasia grade 2 or higher (CIN2+): CO2 gas-based cryotherapy, non-gas cryotherapy, and thermal ablation (TA). Here, we present findings regarding the incidence of sexually transmitted infections (STI) and vaginitis post-treatment. Samples were collected at enrollment and again at 6 weeks post-treatment and assessed for STIs (Chlamydia trachomatis (CT), Neisseria gonorrhea (NG), and Trichomonas vaginalis (TV)) and vaginitis (Bacterial vaginosis (BV) and/or Candida albicans (Candida)). This analysis reflects 864 women with baseline and 6-week follow-up data. None of the ablative treatments put women at increased risk for STIs (CT, NG, TV) or vaginitis (BV, Candida). While most women adhered to post-treatment recommendations (97%) and no difference by treatment arm was observed, the incidence of STIs at follow-up in women that did not adhere with a given recommendation was higher compared to their adherent counterparts. The incidence of gynecologic infection did not increase with any of the ablation treatments from baseline to the six-week follow-up. Non-gas cryotherapy and TA emerge as safe alternatives to gas-based cryotherapy with respect to gynecologic infection rates.